Legal Examination of Choosing the Law Governing the Contracts by Cosignatories in International Private Law - Ã™Â‚Ã˜Â§Ã™ÂÃ›ÂŒ, Ã˜ÂÃ˜Â³Ã›ÂŒÃ™Â†; Ã™ÂˆÃ˜ÂÃ˜Â¯Ã˜ÂªÃ›ÂŒ Ã˜Â´Ã˜Â¨Ã›ÂŒÃ˜Â±Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã˜ÂÃ˜Â³Ã™Â† (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Among the controversial discourses brought up in the field of international private law is the issue of determining the law governing the contracts. Today, from the legal perspective, many believe that, based on sovereignty of will, the signatories of contracts can choose their own ruling law. In this article, mainly the legal (fiqhÄ«) dimension of choosing the law governing the contract by the cosignatories, in the form of condition within the contract, has been reviewed and it is noted whether such a condition is sound and valid or illegal and invalid. It seems that the financial rulings and outcomes of the contracts are typically regarded as among the changeable legal rulings that the two parties can change them by means of condition within the contract or contract by compromise. Thus, in such instances choosing and determining the law governing the contract is permissible and valid. As for the unchangeable rulings, i.e., legal mandatory rules such as eligibility, intention, and consent, however, choosing the governing law by the cosignatories is not valid and they cannot be allowed the option of determining the law.